17-DMAG regulates p21 expression to induce chondrogenesis in vitro and in vivo - Karri L. Bertram; Nadia Narendran; Pankaj Tailor; Christina Jablonski; Catherine Leonard; Edward Irvine; Ricarda Hess; Anand O. Masson; Saleem Abubacker; Kristina Rinker; Jeff Biernaskie; Robin M. Yates; et al. (The Company of Biologists, 2018)
Cartilage degeneration after injury affects a significant percentage of the population, including those that will go on to develop osteoarthritis (OA). Like humans, most mammals, including mice, are incapable of regenerating injured cartilage. Interestingly, it has previously been shown that p21 (Cdkn1a) knockout (p21−/−) mice demonstrate auricular (ear) cartilage regeneration. However, the loss of p21 expression is highly correlated with the development of numerous types of cancer and autoimmune diseases, limiting the therapeutic translation of these findings. Therefore, in this study, we employed a screening approach to identify an inhibitor (17-DMAG) that negatively regulates the expression of p21. We also validated that this compound can induce chondrogenesis in vitro (in adult mesenchymal stem cells) and in vivo (auricular cartilage injury model). Furthermore, our results suggest that 17-DMAG can induce the proliferation of terminally differentiated chondrocytes (in vitro and in vivo), while maintaining their chondrogenic phenotype. This study provides new insights into the regulation of chondrogenesis that might ultimately lead to new therapies for cartilage injury and/or OA.